Pengobatan antimalaria klorokuin sebagai terapi penyakit Systemic Lupus Erythematosus (SLE) - Maulidia, Fadillah (Wellness And Healthy Magazine, 2020)
Systemic lupus erythematosus (SLE) is a multi-system autoimmune disease that attacks various organs. Antimalarial agents are part of an immunomodulatory regimen that is used to cure patients with SLE. Not all antimalarial agents can be used in the treatment of lupus; This review lends to the study of the use of chloroquine. Overall, antimalarial drugs have many beneficial effects in patients with SLE, and have a good safety profile. According to the American College of Rheumatology (ACR) the diagnosis of SLE was originally established to be found at least 2 or more than 11 criteria. The classification degrees are divided into mild, moderate and severe SLE. The recommended use of base chloroquine 3.5-4.0 mg / kg BW / day (150-300 mg / day) is only used in mild SLE.